2010
DOI: 10.1149/1.3428667
|View full text |Cite
|
Sign up to set email alerts
|

Relating Synthesis Conditions and Electrochemical Performance for the Sodium Intercalation Compound Na[sub 4]Mn[sub 9]O[sub 18] in Aqueous Electrolyte

Abstract: The sodium intercalation compound Na4Mn9normalO18 , more commonly Na0.44MnO2 , was studied as a potential positive electrode in an aqueous electrolyte hybrid energy storage device. Varying ratios of precursors were used in a solid-state synthetic route in an effort to compensate for volatile loss of sodium during processing. The powders were characterized using X-ray powder diffraction and thermogravimetric analysis, while particle morphology and formation were studied by scanning electron microscopy/electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 18 publications
2
61
1
Order By: Relevance
“…2a and 2b show the needle-like morphology of Na 0.44 MnO 2 which was consistent with literatures. 15,16,20 Fig. 2c and 2d show the surface morphology of carbon coated NaTi 2 (PO 4 ) 3 where there is a thin layer of graphite covering the particles of NaTi 2 (PO 4 ) 3 which was introduced during precursor preparations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a and 2b show the needle-like morphology of Na 0.44 MnO 2 which was consistent with literatures. 15,16,20 Fig. 2c and 2d show the surface morphology of carbon coated NaTi 2 (PO 4 ) 3 where there is a thin layer of graphite covering the particles of NaTi 2 (PO 4 ) 3 which was introduced during precursor preparations.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Since Dahn's group first reported VO 2 /LiMn 2 O 4 system with aqueous electrolyte in 1990s, 9,10 many groups studied potential electrode materials which are viable in aqueous electrolyte: LiV 3 4 . 6,[11][12][13][14] Their sodium analogs also show attractive performance: the activated carbon Na 0.44 MnO 2 hybrid system has demonstrated good cycle stability over 1000 cycles, 15,16 NaTi 2 (PO 4 ) 3 /Na 0.44 MnO 2 system has demonstrated good rate capabilities. 17 However, capacity fading of aqueous cells is often reported in the literature with different electrode material systems.…”
mentioning
confidence: 99%
“…Aqueous lithium-ion batteries using cathode materials adopted from commercialized organic electrolyte cells have been explored, but in general they have shown limited cycle life [6][7][8] . Aqueous sodium cells using a Na x MnO 2 cathode and a capacitive carbon anode have been demonstrated to offer long cycle life, but have limited rate capability 9,10 . These aqueous battery technologies have been limited primarily by the development of anode materials that have the correct potential and that are chemically stable at the desired electrolyte pH 11 .…”
mentioning
confidence: 99%
“…on the O 2-sites, 10,11) other alkali cations, 12,13) and different electrolyte systems have been employed to improve the performance of Lithium ion batteries. [14][15][16] In our previous works, 17,18) we demonstrated that the one-dimensional (1-D) nanosized cathode materials have superior rate performance than the commercial micron-sized powder due to larger contact area with the electrolyte, shorter distance for lithium ion transport, and higher electronic pathway.…”
Section: mentioning
confidence: 99%